Physiological and toxic effects of selenium on seed germination of cowpea seedlings - Lapaz, Allan de Marcos [UNESP]; Melo Santos, Luiz Felipe de [UNESP]; Pereira Yoshida, Camila Hatsu; Heinrichs, Reges [UNESP]; Campos, Marcelo; Reis, Andre Rodrigues dos (Inst Agronomico, 2019)
Selenium (Se) is considered a beneficial chemical element for plants, but in high concentrations it may present symptoms of toxicity. The present study aimed to evaluate 11 concentrations of Se (0; 0.1; 0.5; 1; 5; 10; 20; 40; 80; 400; 800 mg.L-1) to determine the low and high (toxicity) critical levels to seed germination of cowpea (Vigna unguiculata). In addition, alterations in the rate of photosynthetic pigments, lipid peroxidation and sugars during the initial growth development of seedlings were analysed. Seeds exposed to 800 mg.L-1 of Se showed a decrease of 20% of seed germination index compared to the control treatment. The decrease in seedling growth reflected in the increase of total sugars and sucrose concentration in both the shoot and root in response to exposure to Se concentration. There was a decrease in the concentration of leaf chlorophyll, carotenoids and pheophytin from seedlings exposed to high Se concentration. The rate of lipid peroxidation and the hydrogen peroxide concentration in the shoot was reduced up to the concentration of 1 mg.L-1 with subsequent increase in response to Se concentration applied. In the roots, the lipid peroxidation rate increased at concentrations higher than 80 mg.L-1. The highest oxidation rate of the cellular lipid membrane in response to Se occurred in the shoot, due to oxidation reactions in the chloroplast. Degradation of photosynthetic pigments and accumulation of total sugars and sucrose can be considered efficient biomarkers to indicate the toxicity of Se in cowpea seedlings and probably in other crops.
Keywords: soluble sugars; oxidative metabolism; phytotoxicity; Vigna unguiculata